APPLICATION OF ALVARADO SCORING SYSTEM IN DIAGNOSIS OF ACUTE APPENDICITIS - Khan, Ikramullah; Rehman, Ata ur (Journal of Ayub Medical College Abbottabad, 2005)
Background: In conditions like acute appendicitis it is impractical to have definitive diagnosis by gold standard test (histopathology) before surgery, we would like a simple test like Alvarado scoring system which depends on the presence and absence of certain variables and which provides an accurate guide to whether or not the patient has the condition. This study was conducted to evaluate Alvarado scoring system for the diagnosis of acute appendicitis in our set up. Methods: 100 consecutive patients with suspected acute appendicitis admitted in Surgical B unit, Khyber Teaching Hospital Peshawar, during the period from July to December 2003 were included in the study. They were given specific scores according to the variables of Alvarado scoring system and then divided into 3 groups. Group 1 patients (score 7 or more) underwent surgery, group 2 patients (score 5-6) were admitted for observation and group 3 patients (score 4 or less) were discharged home. Patients from group 2 with increased symptom intensity (score 7 or more) in reevaluation underwent surgery. Diagnosis was confirmed by histopathological examination. Reliability of scoring system was assessed by calculating negative appendicectomy rate and positive predictive value. Results: Out of a total 100 patients 64 patients underwent surgery and appendicitis was confirmed in 54 cases, thus giving negative appendicectomy frequency of 15.6% (male 12%, female 17.9%). Perforation rate was 7.8%. Positive predictive value was 84.3% (males 88%, females 82.1%). Conclusion: This scoring system is easy, simple and cheap complementary aid for supporting the diagnosis of acute appendicitis especially for junior surgeons. Key words: Acute appendicitis, Appendicectomy, Scoring system.